Leveraging Software Engineering Principles: An IT-Enabled Component-Based Knowledge Management Model for Healthcare Information Systems in Developing Countries - Arshad, Arfan; Ghaffar, Abid; Siddqiue, Muhammad Usman; Sultan, Syed Ali; Manzoor, Asim (VFAST Transactions on Software Engineering, 2025)
In the contemporary era, the integration of Information Technology (IT) with Knowledge Management (KM) infrastructures has significantly transformed the healthcare sector. This study investigates the current use and effectiveness of IT in supporting KM functions within public-sector healthcare organizations in Pakistan. It further explores and evaluates key factors influencing the success of KM practices in this context. Employing a triangulated mixed-method approach, the research examines the maturity level of KM within healthcare information systems (HCIS) and the general understanding of KM concepts among stakeholders. Empirical findings reveal that most of the proposed hypotheses were statistically significant, except for two: the impact of exogenous factors on KM specifications and the impact of KM success on overall organizational performance, which were found to be weak and non-significant. A conceptual model was initially develop based on the hypothesized relationships, followed by an empirical model tested through Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess significance (p < 0.05) and model fit. Based on these analyses, the study proposes an integrated, component-based KM model aimed at enhancing the governance and effectiveness of HCIS.